Kropak Ferrara: Reconsidering The 16th Century Javanese Muslim Identity - Syamsul Idul Adha (Tashwirul Afkar, 2021)
Abstrak Penelitian ini bertujuan menganalisis fungsi teks Kropak Ferrara sebagai penanda konstruksi historisitas dan pembentuk sistem nilai Islam-Jawa pada abad ke-16 M. Naskah Kropak Ferrara yang dikaji adalah Naskah MS Cod. Or. 10.811 yang dipublikasikan oleh G.W.J. Drewes. Penelitian ini menggunakan analisis Semiotik dan Analisis Semantik Linguistik untuk menganalisis hubungan antara teks penanda dan realitas historis Islam-Jawa. Hasil penelitian menunjukkan bahwa penggunaan sistem aksara dan bahasa Jawa dalam teks penanda sebagai suatu proses peralihan latar belakang kultur Jawa dari periode Hindu-Buddha menuju sistem tatanan masyarakat Islami yang dikembangkan melalui keberagaman identitas kultur Muslim di Pantai Utara Jawa. Teks Penanda juga menunjukkan bahwa adanya ancaman kewujudan identitas Islam-Jawa melalui perkembangan doktrin Monisme yang merupakan bagian dari unsur-unsur Tantra dan ditanggapi oleh Kropak Ferrara melalui pembentukan sistem keyakinan yang didasarkan pada ajaran-ajaran Islam Sunni. Sistem nilai yang dikonstruksikan oleh Kropak Ferrara yang didaptasi dari Bidāyah al-Hidāyah untuk mendukung ortodoksi merupakan suatu antitesis melalui otoritas Giri Kedaton sebagai otoritas tertinggi Islam-Jawa. Kropak Ferrara bukan hanya sumber sejarah dan kultur Muslim Jawa, tetapi juga sebuah teks yang mengkonstruksikan identitas dan kultur masyarakat Islam Jawa yang terpisah dari identitas Jawa pra-Islam. Abstract This article aims to analyze the function of the Kropak Ferrara, the oldest Javano-Islamic manuscript, as an essential lens to examine the 16th century formation of Javanese Islamic system. Based on G.W.J. Drewes’s close examination to the manuscript of Kropak Ferrara (MS Cod. Or. 10.811), the article deploys both Semiotic Analysis and Linguistic Semantic Analysis in order to analyze the relationship between the signifier text and the historical reality of Islam in ancient Javanese. It further argues that the use of the Javanese script and language system, hereby spelled as the signifier text, is a conversion of Javanese cultural settings from the Hindu-Buddhist period to the order of Islamic community that developed along with diverse cultural Muslim identities on the North Coast of Java. The signifier text also informs us the tension between the earliest Javanese Islamic identity through the development of Monism doctrine which is essential part of Tantrā doctrine and Kropak Ferrara which dictates the provisions of Sunni Islam. The fundamental Islamic belief with which Kropak Ferrara dictates is indeed an adaptation of the classical theological book Bidāyah al-Hidāyah which encourages Islamic orthodoxy as an antithesis to Monism. It culminated to Giri Kedaton’s authority which resorted as the highest religious authority of Islam in Java. Not only does Kropak Ferrara serve as a historical source important to understand cultural aspect of the earliest Muslim community in Java, but also resorts as a the fundamental textual tradition which is essentilal in imposing the identity and culture of the earliest Javanese Muslim community and at the same time to distance the community from pre-Islamic identity.